Credit and Money in a Search Model with Divisible Commodities - Shouyong Shi (Queen's University, Department of Economics, 1995)
This paper examines the competition between money and credit in a search model with divisible commodities. It is shown that flat money can be valuable even though it yields a lower rate of return than the coexisting credit. The competition between money and credit increases efficiency. The monetary equilibrium with credit Pareto dominates the monetary equilibrium without credit whenever the two coexist. When a credit is repaid with money, the competition also bounds the purchasing power of money from below by that of credit. In so doing it eliminates the weak monetary equilibrium found in previous search models. With numerical examples, we rank three different monetary equilibria and examine the properties of the interest rate.
Keywords: E40; C78; 330; search; money; credit; return dominance